Pengaruh Program PEKA JIWA Terhadap Pengetahuan, Keterampilan dan Skor Kecemasan akademik Remaja - Husna, Zumairoh Miftahul; Estria, Suci Ratna; Suparti, Sri; Elsanti, Devita (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2025)
Academic anxiety is a psychological problem often experienced by adolescents and negatively impacts achievement and mental health if not handled properly. Academic anxiety problems have a high prevalence. The purpose of this study was to determine the effect of the Peduli Akan Kesehatan Jiwa (PEKA JIWA) program on the knowledge, skills, and academic anxiety scores of adolescents at SMA Negeri 1 Patikraja, Banyumas. The research design used was a pre-experimental one-group pretest-posttest approach. A sample of 60 respondents was selected using a total sampling technique. The research instruments included a knowledge questionnaire developed by the researcher, an academic anxiety questionnaire adopted from Cassady (2019), and a coping skills observation sheet with interventions in the form of academic anxiety education and Butterfly Hug and Mindfulness exercises that had undergone feasibility testing. The results of the analysis using the Wilcoxon signed-rank test showed a significant increase in knowledge scores from an average of 9.86 to 11.60, Butterfly Hug skills from 2.61 to 4.96, and Mindfulness from 4.65 to 7.68, and academic anxiety scores from 30.40 to 25.28. The Wilcoxon test obtained a p value <0.000 (p <0.05). The PEKA JIWA program is effective in increasing knowledge and coping skills and reducing academic anxiety in adolescents.